(untitled) (Bangladesh Journal of Plant Taxonomy, 2018)
The present study was conducted to delineate Diplazium Swartz species based on leaf architecture. Using PAleontological STatistics (PAST), a cluster and Principal Component Analysis of leaf architecture characters of 27 selected Diplazium species at the Philippine National Herbarium (PNH) was done. The dendogram (cophenetic correlation = 0.8436) and principal component analysis supported the four clusters of Diplazium using leaf architecture characters. At Gower distance of 0.25, Diplazium species were categorized as: Cluster 1 (Cladodromous – short stalked, stout and massive 1° vein); Cluster 2 (Reticulodromous – long stalked, moderate 1° vein); Cluster 3 (Craspedodromous – long stalked, stout to massive 1° vein); and Cluster 4 (Craspedodromous – short stalked, stout to massive 1° vein). The unifying characters were apex shape, base symmetry and 1° vein category, while the significant differentiating characters were 2° vein angle of divergence and variation in the 2° vein angle of divergence, 3° vein category, 3° vein angle of divergence, variation in 3° vein angle of divergence, 3° vein spacing and lobation. The successful delineation of Diplazium species proved that leaf architecture can be a good taxonomic marker and could be an alternative way of identifying species in the absence of sori.